Computer prediction of fracture of magnesium alloy cylindrical billet during equal channel angular pressing - Elena P. Volkova; Gandzhina D. Khudododova; Aleksandr V. Botkin; Ruslan Z. Valiev (Frontier Materials & Technologies)
The main challenge in using magnesium alloys, applied in medicine as biodegradable materials, is their difficult deformability, which in turn leads to frequent failure of samples during severe plastic deformation. This paper shows that the temperature mode of equal channel angular pressing (ECAP) of a Mg–Zn–Ca system magnesium alloy, which ensures deformation of samples without failure, can be determined based on the results of finite-element computer simulation of the stress-strain state of the billet, calculation of alloy damage using the Cockcroft–Latham model, and prediction of the sample failure area. Modelling showed that the surface area of the billet adjacent to the matrix inner corner during ECAP, is the area of possible failure of the magnesium alloy. The value of alloy damage during ECAP in this area at T=350 °C is less than 1, which corresponds to non-failure of the metal. To verify the computer simulation results, ECAP physical simulation was performed; billets without signs of failure were produced. A study of the mechanical properties of the Mg–1%Zn–0.06%Ca magnesium alloy was conducted before and after ECAP processing according to the selected mode: the ultimate strength limit increased by 45 %, the hardness increased by 16 %, while the plasticity increased by 5 %.